Melanocortin Regulation of Inflammation - Wang, Wei; Guo, Dong-Yu; Lin, Yue-Jun; Tao, Ya-Xiong (Frontiers in Endocrinology, 2019)
Adrenocorticotropic hormone (ACTH), and -, -, and -melanocyte-stimulating hormone (-, -, -MSH), collectively called melanocortins or melanocortin peptides, together with their receptors (melanocortin receptors), are components of an ancient modulatory system. The clinical use of ACTH in the treatment of rheumatoid arthritis started in 1949, originally thought that the anti-inflammatory action was through hypothalamus-pituitary-adrenal axis and glucocorticoid-dependent. Subsequent decades have witnessed extensive attempts in unraveling the physiology and pharmacology of the melanocortin system. It is now known that ACTH, together with -, -, and -MSHs, also possess glucocorticoid-independent anti-inflammatory and immunomodulatory effects by activating the melanocortin receptors expressed in the brain or peripheral immune cells. This review will briefly introduce the melanocortin system and highlight the action of melanocortins in the regulation of immune functions in in vitro, in vivo, preclinical and clinical studies. The potential therapeutic use of melanocortins are also summarized.